FRONTIER POSITION AND MEANING PRODUCTION IN THE INDIGENOUS MATHEMATICS EDUCATION - Luci dos Santos Bernardi; Ademir Donizeti Caldeira; Claudia Glavam Duarte (Editora da Universidade de Santa Cruz do Sul, 2013)
This paper presents some results of a survey that aimed to follow a process of continuous formation of a group of Kaingang indigenous teachers who teach mathematics in Terra Indigena Xapecó in Ipuaçu, SC. This research sought promote reflection on the challenges of Indigenous Education in the construction of an educational process in mathematics education, specifically that the construction of this educational process, contemplating the traditional mathematics and mathematics education. Examined the issue of frontier position of the teacher indigenous dealing with diversity and cultural conflicts, background and foreground, and the construction of meanings of mathematics in mathematics indigenous education. For this, we seek the theorical support in Critical Mathematics Education and in Ethnomathematics. The research showed us that one of the ways to minimize the challenges confronted would be to soften the boundaries between indigenous and non indigenous people while strengthening the identity markers, a new logic to understand the meaning construction for elements of their culture.